2008
DOI: 10.1074/jbc.m708226200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1 Induces αvβ3 Integrin Expression in Human Lung Fibroblasts via a β3 Integrin-, c-Src-, and p38 MAPK-dependent Pathway

Abstract: In response to transforming growth factor ␤1 (TGF␤) stimulation, fibroblasts modify their integrin repertoire and adhesive capabilities to certain extracellular matrix proteins. Although TGF␤ has been shown to increase the expression of specific ␣v integrins, the mechanisms underlying this are unknown. In this study we demonstrate that TGF␤1 increased both ␤3 integrin subunit mRNA and protein levels as well as surface expression of ␣v␤3 in human lung fibroblasts. TGF␤1-induced ␣v␤3 expression was strongly adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 43 publications
(73 reference statements)
4
72
0
Order By: Relevance
“…Analysis of the integrin a V b 3 promoter revealed many Sp1 binding sites that are important for integrin a V b 3 transcription in B16 and A375 cells. It was reported that Sp1 could regulate the transcriptional activity of integrin a V b 3 (Tajima et al, 2000;Pechkovsky et al, 2008). We also confirmed in our study that knocking down Sp1 in B16-As and A375-sh cells by using siRNA reduced the expression of integrin a V b 3 , as well as the adhesion and invasion abilities of melanoma cells (Figures 5a-e).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analysis of the integrin a V b 3 promoter revealed many Sp1 binding sites that are important for integrin a V b 3 transcription in B16 and A375 cells. It was reported that Sp1 could regulate the transcriptional activity of integrin a V b 3 (Tajima et al, 2000;Pechkovsky et al, 2008). We also confirmed in our study that knocking down Sp1 in B16-As and A375-sh cells by using siRNA reduced the expression of integrin a V b 3 , as well as the adhesion and invasion abilities of melanoma cells (Figures 5a-e).…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that transcription factors AP-1, Ets-1 and Sp1 bind to integrin a V and b 3 promoter regions and regulate integrin a V and b 3 transcription (Tajima et al, 2000;Rothhammer et al, 2004;Pechkovsky et al, 2008;Lossner et al, 2009). To address how JWA knockdown upregulates integrin a V b 3 , RT-PCR was used to determine the mRNA levels of these transcription factors after JWA knockdown.…”
Section: Jwa Suppresses Cell Invasion and Matrix Metalloproteinases (mentioning
confidence: 99%
“…In other species, TGFB has been linked to indirect role(s) in trophoblast attachment and invasion by enhancing production of ECM proteins such as oncofetal-fibronectin (Feinberg et al 1994), inducing expression of ITGs (Zambruno et al 1995, Kagami et al 1996, Lai et al 2000, Pechkovsky et al 2008, and inhibiting trophoblast invasion by reducing production of proteases such as MMPs and plasmin (Graham & Lala 1991, Graham 1997, Kallapur et al 1999, Karmakar & Das 2002. Similar actions of TGFB may also be involved in peri-implantation events in pigs.…”
Section: Tgfb Lap and Integrins In Porcine Implantationmentioning
confidence: 98%
“…Y654-␤-catenin is a known target of Src kinase, and Src family kinase activation is reported downstream of TGF␤1 in several models (7,10,16). Indeed Src kinase(s) activation proved crucial for TGF␤-induced phosphorylation of ␤-catenin.…”
Section: Py654-␤-catenin Accumulation Is Src Kinase-dependent-mentioning
confidence: 99%